1984
DOI: 10.1037/0021-9010.69.3.437
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of management styles in business and nonbusiness organizations.

Abstract: Bass and Valenzi (1974) postulated that power and information are major factors m determining the extent to which five leadership styles are used and presented a set of hypotheses concerning the way power and information affect these styles. This study set out to test the Bass-Valenzi hypothesis and to analyze the impact, if any, of aggregating data from business and nonbusiness organizations on the results. It found that the effect of power and information was not the same across organizations. In business or… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

1985
1985
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 5 publications
1
4
0
Order By: Relevance
“…Further work (Bass et a/. 1975, Shapira 1976, Chitayat and Venezia 1984 confirmed the validity of the scales, but also showed high correlation among all measures except delegation and direction (Shapira 1976). This suggested that these two scales alone would provide two independent measures of key components of supervisory style.…”
Section: Supervisory Style-direction/delegationsupporting
confidence: 70%
“…Further work (Bass et a/. 1975, Shapira 1976, Chitayat and Venezia 1984 confirmed the validity of the scales, but also showed high correlation among all measures except delegation and direction (Shapira 1976). This suggested that these two scales alone would provide two independent measures of key components of supervisory style.…”
Section: Supervisory Style-direction/delegationsupporting
confidence: 70%
“…Each of these characteristics limits the generalization of the results (Chitiyat & Venezia, 1984). Furthermore, Sagie et al did not examine the effect of PDM and decision type on performance.…”
Section: Strategic and Tactical Decisionsmentioning
confidence: 95%
“…The simulated organization in this study was of an academic, nonwork nature (Evans, 1970). Would the results also hold in simulated business settings (Chitayat & Venezia, 1984)? Would they hold in real (i.e., long-term) organizations?…”
mentioning
confidence: 86%